Clinicopathological significance of tumor-infiltrating lymphocytes and programmed death-1 expression in cutaneous melanoma: a comparative study on clinical subtypes. Issue 5 (October 2018) - Lee, Woo J.; Lee, Ye J.; Shin, Ho J.; Won, Chong H.; Chang, Sung E.; Choi, Jee H.; Lee, Mi W.
Abstract : Interactions between immune cells and tumor cells play an important role in tumor progression. We evaluated patterns of tumor-infiltrating lymphocytes (TILs) and programmed death-1 (PD-1) expression in acral and nonacral cutaneous melanoma, and determined their effects on clinicopathological characteristics and biologic responses. We identified 122 cases of cutaneous melanoma, of which 39 were cases of non-nail unit acral melanoma (NNUAM), 35 were cases of nail unit melanoma (NUM), and 48 were cases of nonacral melanoma. Clinicopathological features and survival outcomes were analyzed according to the scores for TILs and PD-1 expression in intratumoral and peritumoral compartments. The effects of the presence of TILs and PD-1 expression on various clinicopathological factors differed according to the clinical subtypes of cutaneous melanoma. The frequency of intratumoral TILs and PD-1 expression were lower in NUM than in the other two subtypes. The density of peritumoral PD-1 was significantly higher in NNUAM. In NUM and nonacral melanoma, a low density of intratumoral TILs and PD-1 was associated with a deeper Breslow thickness and the presence of a vertical growth phase. In NNUAM, a high density of peritumoral TILs and PD-1 was associated with a shallower Breslow thickness and less frequent extracutaneous dissemination. In NNUAM, a high density of peritumoral PD-1 was associated with a better prognosis. This study suggests that the effects of PD-1+ TILs on biological activity differ according to the clinical subtypes of cutaneous melanoma.